Comments on "The Tropospheric Land-Sea Warming Contrast as the Driver of Tropical Sea Level Pressure Changes" - Makarieva, A.M.; Gorshkov, V.G.; Nefiodov, A.V.; Sheil, D.; Nobre, A.D.; Li, B.L. (American Meteorological Society, 2015)
In their paper “The tropospheric land–sea warming contrast as the driver of tropical sea level pressure changes,” Bayr and Dommenget proposed a simple model of temperature-driven air redistribution to quantify the ratio between changes of sea level pressure ps and mean tropospheric temperature Ta in the tropics. This model assumes that the height of the tropical troposphere is isobaric. Here problems with this model are identified. A revised relationship between ps and Ta is derived governed by two parameters—the isobaric and isothermal heights—rather than just one. Further insight is provided by the earlier model of Lindzen and Nigam, which was the first to use the concept of isobaric height to relate tropical ps to air temperature, and they did this by assuming that isobaric height is always around 3 km and isothermal height is likewise near constant. Observational data, presented here, show that neither of these heights is spatially universal nor does their mean values match previous assumptions. Analyses show that the ratio of the long-term changes in ps and Ta associated with land–sea temperature contrasts in a warming climate—the focus of Bayr and Dommenget’s work—is in fact determined by the corresponding ratio of spatial differences in the annual mean ps and Ta. The latter ratio, reflecting lower pressure at higher temperature, is significantly impacted by the meridional pressure and temperature differences. Considerations of isobaric heights are shown to be unable to predict either spatial or temporal variation in ps. As noted by Bayr and Dommenget, the role of moisture dynamics in generating sea level pressure variation remains in need of further theoretical investigations.